Major trends in the development of industrial areas of Budapest in the early 21st century - Kiss, Éva (Hungarian Geographical Bulletin, 2009)
Budapest bore witness to dramatic changes in its industry following 1989, and these have had a major impact on the location of industry and on the use of former industrial areas. The main purpose of this study serves to illustrate the major developments and shifts that took place within the traditional industrial areas during the last decade and is based upon the results of a survey carried out in 2006, in order to reveal the extent of the functional transformation of areas that were traditionally industrial in nature. Over the last decade the former processes (deindustrialisation, rehabilitation, shrinkage of industrial areas, and change in their functions) have developed, albeit at a different pace spatially. As a consequence, the spatial pattern of the Hungarian capital, as well as its functional divisions have undergone significant transformation.